Imunoscintigrafické vysetrrení kostní drenĕ u hematologických nemocných - Maturová, M; Bláha, V; Kolínská, J (Vnitrni lekarstvi, 1997)
In 36 patients with different haematological diseases the authors examined by immunoscintigraphy the bone marrow using the 99mTc preparation Scintimun Granulozyt of Behring Co. They studied the distribution of haematopoietic tissue order to detect deviations from normal, focal defects, elongation of haematopoiesis into the periphery of long bones or extramedullary haematopoiesis. Distribution of haematopoietic tissue was evaluated visually and semiquantitatively.
Keywords: radioimunodetekce; krevní nemoci; Hematopoiesis; hematopoéza; Female; Organotechnetium Compounds; Bone Marrow; Humans; ženské pohlaví; mužské pohlaví; Male; lidé; Middle Aged; lidé středního věku; organotechneciové sloučeniny; Hematologic Diseases; Radioimmunodetection; kostní dřeň